Khel khelony class 1 - Maryam, Shera; Fozia, Rizwan (book group Karachi, 2001)
a popular Urdu textbook for Class 1 students in Pakistan. It's designed to introduce young learners to basic Urdu reading, writing, and comprehension skills in a fun and engaging way.